São Carlos: from urban formation to the arrival of the railway - Frascareli, Marina Biazotto; Fiorin, Evandro; Romão, Kauê Marques (National Journal of City Management, 2023)
This article discusses the origin of the urban nucleus of São Carlos-SP, as well as the importance of the insertion of the railroad for socioeconomic development and for urban transformations of the municipality. The problem originates from the dismantling of rail transport that has its central urban equipment converted into spaces without specific destination. In this sense, the text develops a historiographical understanding, through a bibliographical research, about the municipality of São Carlos-SP: from its embryonic period (1857) to the insertion of the railroad (1880) followed by its apogee and decline.